Variants of the aortic arch in adult general population and their association with thoracic aortic aneurysm disease. Issue 7 (14th April 2021) - Yousef, Sameh; Singh, Saket; Alkukhun, Abedalrazaq; Alturkmani, Bilal; Mori, Makoto; Chen, Juliafayanne; Mullan, Clancy W.; Brooks, Cornell W.; Assi, Roland; Gruber, Peter J.; Cortopassi, Isabel; Geirsson, Arnar; et al.
Abstract: Background: Query a single institution computed tomography (CT) database to assess the prevalence of aortic arch anomalies in general adult population and their potential association with thoracic aortopathies. Methods: CT chest scan reports of patients aged 50–85 years old performed for any indication at a single health system between 2013 and 2016 were included in the analysis. Characteristics of patients with and without aortic arch anomalies were compared by t test and Fisher exact tests. Logistic regression analysis was performed to assess for independent risk factors of thoracic aortic aneurysm (TAA). Results: Of 21, 336 CT scans, 603 (2.8%) described arch anomalies. Bovine arch ( n = 354, 58.7%) was the most common diagnosis. Patients with arch anomalies were more likely to be female ( p < .001), non‐Caucasian( p < .001), and hypertensive ( p < .001). Prevalence of TAA in arch anomalies group was 10.8% ( n = 65) compared to 4.1% ( n = 844) in the nonarch anomaly cohort ( p < .001). The highest prevalence of thoracic aneurysm was associated with right‐sided arch combined with aberrant left subclavian configuration (33%), followed by bovine arch (13%), and aberrant right subclavian artery (8.2%). On binary logistic regression, arch anomaly (OR = 2.85 [2.16–3.75]), aortic valve pathology (OR 2.93 [2.31–3.73]), male sex (OR 2.38 [2.01–2.80]), and hypertension (OR 1.47 [1.25–1.73]) were significantly associated with increased risk of thoracic aneurysm disease. Conclusions: Reported prevalence of aortic arch anomalies by CT imaging in the older adult population is approximately 3%, with high association of TAA (OR = 2.85) incidence in this subgroup. This may warrant a more tailored surveillance strategy for aneurysm disease in this subpopulation.